Prove each of the following by the principle of mathematical induction
Attachments:
Answers
Answered by
3
Let '1 + 2 + 2^(2) + ... 2^(n - 1)' be statement P(n).
Note that:
P(n) = 2^(0) + 2^(1) + 2^(2) + ... 2^(n - 1)
For n = 1 : P(1):
LHS: 2^(1 - 1) = 2^(0) = 1
RHS: 2^(1) - 1 = 2 - 1 = 1
As RHS = LHS, P(1) is true for n = 1
Let it be true for n = m, P(m) :
1 + 2 + 2^(2) + ... 2^(m - 1) = 2^(m) - 1
For n = m + 1: P(m + 1): LHS:
=> 1 + 2 + 2^(2) + ... 2^(m+1 - 1)
=> 1 + 2 + 2^(2) + ... 2^(m)
=> 1 + 2 + 2^(2) + ... + 2^(m - 1) + 2^(m)
=> 2^(m) - 1 + 2^(m)
=> 2.2^(m) - 1
=> 2^(m + 1) - 1
RHS:
=> 2^(m + 1) - 1
As both are equal, the given statement is true.
Similar questions